2019
DOI: 10.1039/c9pp00174c
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient, thermostable and cadmium selective firefly luciferase suitable for ratiometric metal and pH biosensing and for sensitive ATP assays

Abstract: The brighter and cadmium sensitive luciferase of Amydetes is suitable for sensitive ATP and biosensing assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
12
0
4
Order By: Relevance
“…The luciferin-luciferase assay is the most commonly used ATP-detection method in studies of antibiotic susceptibility [18-22, 28, 37] as well as the cleanliness of surfaces and medical equipment in healthcare facilities or food industries [32,[38][39][40]. Other methods involve ATP-sensing fluorescent proteins such as engineered luciferase probes expressed on the outer side of the plasma membrane [41,42] or use of fluorescence microscopy for real-time ATP measurement using a two-enzyme system [43].…”
Section: Existing Methods For Atp Detection In Antibiotic Susceptibility and Hygiene Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The luciferin-luciferase assay is the most commonly used ATP-detection method in studies of antibiotic susceptibility [18-22, 28, 37] as well as the cleanliness of surfaces and medical equipment in healthcare facilities or food industries [32,[38][39][40]. Other methods involve ATP-sensing fluorescent proteins such as engineered luciferase probes expressed on the outer side of the plasma membrane [41,42] or use of fluorescence microscopy for real-time ATP measurement using a two-enzyme system [43].…”
Section: Existing Methods For Atp Detection In Antibiotic Susceptibility and Hygiene Testingmentioning
confidence: 99%
“…Online (real time) measurement of eATP in microbial cultures has not yet been described, presumably due to limited stability of the most widely available wild-type luciferases. The half-life of the WT firefly luciferase in assay buffer at room temperature is only 3 h which makes it difficult to use in growth experiments requiring longer time periods of monitoring [32,33]. In the last two decades several engineered firefly luciferases have been described with strongly improved thermostability in buffer [34][35][36].…”
Section: Atp-based Hygiene and Cell Viability Testingmentioning
confidence: 99%
“…Viviani and co-workers reported a technique to estimate the intracellular pH in E. coli using mutant firefly luciferases, 164 as well as a mutant firefly luciferase for ratiometric pH sensing and the selective detection of cadmium. 207 A genetically encoded pH sensitive reporter has also been recently reported that consists of a pH-sensitive GFP (superecliptic pHluorin) that emits at 510 nm, and a pH-stable luciferase Antares that emits at 580 nm. On the addition of furimazine, a ratiometric readout R 580/510 was indicative of pH and this system was shown to be functional both in vitro and in vivo using xenograft murine tumours to detect acidosis.…”
Section: Sensing Of Ph Metal Ions Reactive Oxygen Species (Ros) Enmentioning
confidence: 99%
“…The brightness of BL reaction, which is a function of quantum yield, K m , V max , turnover rate, protein stability, and sensitivity to product inhibition [ 26 ], is another important parameter that has to be considered, for example, in microscopy. In order to overcome the drawbacks of natural enzymes, several brighter analogs of firefly luciferase and luciferases with increased thermostability have been generated with the help of site-directed mutagenesis methods [ 27 ].…”
Section: D-luciferin-dependent Luciferasesmentioning
confidence: 99%